Functional properties of oleoresin extracted from white pepper (Piper nigrum L.) retting waste water - Nurul Shahirah Aziz,; Noor-Soffalina Sofian-Seng,; Wan Aida Wan Mustapha, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was carried out to determine the antioxidant activity, total phenolic content (TPC) and piperine in oleoresin extract of pepper retting waste water. Fresh pepper berries were soaked in distilled water (1:2 w/w) and allowed to ret at four different temperatures: 28, 35, 42 and 49°C for a total of 16 days. The retting waste water was collected on the 4th, 8th, 12th and 16th day and was then subjected to dichloromethane liquid extraction prior to analyses. The results showed that highest (p<0.05) oleoresin yield (271.34 ± 28.09 mg/g), antioxidant activity in DPPH (84.58 ± 4.93%), FRAP assay (49.55 ± 6.11 mM TE/g) and total phenolic content (5.64 ± 0.06 mg GAE/g) obtained at low temperature and shorter days of retting (28°C, day 4). Whilst at high temperature with longer days of retting (49°C, day 16) resulted in significantly higher (p<0.05) piperine content (1.81 ± 0.44%) in the waste water. Thus, the findings showed that the agro-industrial waste water produced during white pepper processing contain valuable bioactive oleoresins and other functional compounds which could be explored in details.